The Challenges and Possibilities of the Open Science for the Libraries and Information Studies - Saarti, Jarmo (Qualitative and Quantitative Methods in Libraries; Vol 7 No 2 (2018): June 2018 Issue, 2019)
The Open Access movement in scientific publishing has been gathering momentum in the European Union and its member states, partly due to the policies of some of its main research funders. Similar policies are being implemented worldwide. Already we have seen encouraging research results on the effects of openness on the dissemination of scientific outputs. As business models of Open Access publishing are still under development, but there already is evidence that open access is becoming a major trend in scientific publishing. Recently the requirement of openness is also set to the research data.